Jacob Mincer, Experience and the Distribution of Earnings - Barry R. Chiswick (Institute for the Study of Labor (IZA), 2003)
This paper reviews Jacob Mincer?s contributions to the analyses of earnings and the distribution of earnings through his pioneering focus on labor market experience or on-the-job training. It begins with a brief discussion of the theoretical literature on the distribution of earnings in the pre-Mincer period, and then discusses his analysis of human capital and earnings developed in his 1957 doctoral dissertation and 1958 Journal of Political Economy (JPE) article. Further analyses of on-the-job training, and in particular estimates of the rate of return from on-the-job training, are presented in his 1962 JPE paper. The synergy between Mincer and Becker during the 1960s is discussed, as is the development of the schoolingearnings function by Becker and Chiswick (1966). Mincer (1974) extended this relationship by incorporating experience to form the ?human capital earnings function? in his Schooling, Experience and Earnings (1974). Subsequent modifications, extensions, tests of robustness and the wide applicability of the human capital earnings functions are presented.
Keywords: D31; J31; J24; B21; 330; human capital; labor market experience; earnings; income distribution; Jacob Mincer; Lohnstruktur; Einkommensverteilung; Bildungsertrag; Bildungsinvestition; Qualifikation; Dogmengeschichte; Theorie; Berufserfahrung